Yahoo Web Search

  1. Sort by

  1. ...it is based of conservation of mass, number of atoms in LHS must equal RHS follow the links below for solution.So balanced...

    1 Answers · Science & Mathematics · 20/01/2013

  2. ...: tan² θ cos² θ + cot² θ sin²θ = 1 LHS = (sin²θ/cos²θ) × cos² θ+ (cos²θ/sinθ²...

    1 Answers · Science & Mathematics · 01/10/2013

  3. ...1/tanA = cotA sin(2A) = 2 * sinA * cosA LHS tanA + cotA RHS 2/(2 sinA * cosA) =...

    1 Answers · Science & Mathematics · 29/07/2009

  4. ... sign, try to make the right hand side (RHS) equal the left hand side (LHS). To start, just pick one variable for one side, and put the others on the...

    2 Answers · Science & Mathematics · 11/09/2012

  5. ...the transistor emitter current is I*Rs/100 (100 ohm resistor at top LHS of diagram.) For large current gains in the transistor, the collector current...

    1 Answers · Science & Mathematics · 16/06/2015

  6. r(t) = e^-t costi + e^-t sintj + e^-tk This shows that point (x, y, z) is parametrically (e^-t cost, e^-t sint, e^-t) LHS= z^2= e^2t RHS= x^2 + y^2= e^2t( cos^2t + sin^2t )= e^2t So vector lies on cone

    1 Answers · Science & Mathematics · 25/09/2014

  7. ... to perform it the other way round, i.e. starting from the LHS. A final point is notice that A^2+B^2=R^2((sin^2...

    1 Answers · Science & Mathematics · 25/04/2013

  8. ...sec(3x)*tan(3x) Since M_y is not equal to N_x, the LHS of the equation is not an exact differential, and some other method of solution woulld...

    1 Answers · Science & Mathematics · 13/02/2014

  9. ...this to be true for k = 1 and k = k + 1 Consider k = 1 ------------------------ LHS = 3 RHS = 3 Thus true Consider k = k + 1...

    1 Answers · Science & Mathematics · 18/05/2012

  10. ...x(t-to)) which is equal to y(t-to)(replace t by to in the RHS and LHS of the equation y(t-to) = = sin(x(t-to))). It is obvious from the relation...

    1 Answers · Science & Mathematics · 28/01/2014

  1. Try asking your question on Yahoo Answers